2011
DOI: 10.1007/s00421-011-2058-1
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue after short (100-m), medium (200-m) and long (400-m) treadmill sprints

Abstract: The aim of this study was to compare the aetiology of neuromuscular fatigue following maximal sprints of different distances. It was hypothesized that increasing the distance would modify the type of peripheral and induce central fatigue. 11 subjects performed 100-, 200- and 400-m sprints on a motorized instrumented treadmill. Neuromuscular function, evaluated before (Pre), 30 s after (Post), and 5 and 30 min after the sprints (Post5 and Post30), consisted in determining maximal voluntary knee extensors torque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
7
10
1
6
Order By: Relevance
“…The speed deceleration and the post-exercise blood lactate and blood pH levels indicate that the subjects made an allout effort. In line with previous studies [6,7], adults showed a decrease in MVc torque (-16.1%) after the run. children and adolescents presented no change in MVc despite the loss of running speed, which might be due to faster recovery before the post-fatigue tests.…”
Section: Main Findingssupporting
confidence: 92%
See 4 more Smart Citations
“…The speed deceleration and the post-exercise blood lactate and blood pH levels indicate that the subjects made an allout effort. In line with previous studies [6,7], adults showed a decrease in MVc torque (-16.1%) after the run. children and adolescents presented no change in MVc despite the loss of running speed, which might be due to faster recovery before the post-fatigue tests.…”
Section: Main Findingssupporting
confidence: 92%
“…Thus, in line with the recent study by Tomazin et al [7], the peripheral fatigue could have been caused by the processes beyond the sarcolemma. consistently with earlier studies [4,6], both adolescents and adults showed a decrease in MRTD that is limited by the rate of crossbridge transition from the weakly to strongly bound state [25].…”
Section: Peripheral Fatiguesupporting
confidence: 85%
See 3 more Smart Citations